1999
DOI: 10.1212/wnl.53.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Genetic heterogeneity in Italian families with familial hemiplegic migraine

Abstract: Genetic heterogeneity of FHM has been shown in familial and sporadic FHM patients of Italian origin. The new missense mutation-G4644T-is associated with milder clinical features compared with typical FHM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(51 citation statements)
references
References 25 publications
2
49
0
Order By: Relevance
“…Only two FHM mutations are in S5-S6 linkers, and are in the selectivity filter sequence: T666M in domain II, associated with an ataxic phenotype, 12 and V1457L in domain III, with no details of the associated clinical picture. 11 Furthermore, it should be noted that two out of three NTR CACNA1A mutations carried by ataxic mice, tottering (tg) and rocker (rkr), have a location similar to that of human NTR mutations, namely tg in S5-S6 linker of the II repeat 37 and rkr in S5-6 linker of the III repeat 38 ( fig 2). Of the three EA2 mutations located outside the preferential areas, one (R2136C, identified in the present study) is in the COOH tail upstream of the polyglutamine repeat.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Only two FHM mutations are in S5-S6 linkers, and are in the selectivity filter sequence: T666M in domain II, associated with an ataxic phenotype, 12 and V1457L in domain III, with no details of the associated clinical picture. 11 Furthermore, it should be noted that two out of three NTR CACNA1A mutations carried by ataxic mice, tottering (tg) and rocker (rkr), have a location similar to that of human NTR mutations, namely tg in S5-S6 linker of the II repeat 37 and rkr in S5-6 linker of the III repeat 38 ( fig 2). Of the three EA2 mutations located outside the preferential areas, one (R2136C, identified in the present study) is in the COOH tail upstream of the polyglutamine repeat.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…12 ). Several missense variants in pore-loop regions have been described in the medical literature so far [12][13][14][15][16][17][18][19][20][21][22][23][24] . Structural changes in pore-loop regions can lead to functional changes disabling activation or inactivation of calcium flux 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Familial hemiplegic migraine (FHM) is a rare autosomal dominant-type migraine with aura which is inherited by dominant trait, even though there are reports of sporadic occurrence [1][2][3][4]. A single familial hemiplegic migraine locus has been previously mapped to chromosome 19p13.1 [3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…A single familial hemiplegic migraine locus has been previously mapped to chromosome 19p13.1 [3][4][5][6][7][8][9][10][11][12][13]. Studies in different FHM families showed that additional causative genes must reside in other regions of the genome, including the long arm of chromosome 1 [5,8,9,12,14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation